Plant 4/1 protein: potential player in intracellular, cell-to-cell and long-distance signaling - Morozov, Sergey; Makarova, Svetlana; Erokhina, Tatyana; Kopertekh, Lilya; Schiemann, Joachim; Owens, Robert; Solovyev, Andrey (Frontiers in Plant Science, 2014)
Originally isolated as a result of its ability to interact with the movement protein of Tomato spotted wilt virus in a yeast two-hybrid system, the 4/1 protein is proving to be an excellent tool for studying intracellular protein trafficking and intercellular communication. Expression of 4/1 in vivo is tightly regulated, first appearing in the veins of the cotyledon and later in the vasculature of the leaf and stem in association with the xylem parenchyma and phloem parenchyma. Structural studies indicate that 4/1 proteins contain as many as 5 coiled-coil (CC) domains; indeed, the highest level of sequence identity among 4/1 proteins involves their C-terminal CC domains, suggesting that protein-protein interaction is important for biological function. Recent data predict that the tertiary structure of this C-terminal CC domain is strikingly similar to that of yeast protein She2p; furthermore, like She2p, 4/1 protein exhibits RNA-binding activity, and mutational analysis has shown that the C-terminal CC domain is responsible for RNA binding. The 4/1 protein contains a nuclear export signal. Additional microscopy studies involving leptomycin and computer prediction suggest the presence of a nuclear localization signal as well.